KUALITAS PELAYANAN PERPUSTAKAAN BERDASARKAN PENGELOLAAN KOLEKSI, TATA RUANG, KOMPETENSI PENGELOLA, DAN FASILITAS - Chotibul Umam; Ismiyati ismiyati (JSSH (Jurnal Sains Sosial dan Humaniora), 2020)
Library is one of many place to get knowledge. A management library success can be seen from service quality that give to library customer. Research includes quantitative research. Population this research is all customer Wonosobo Library. Incidental sampling is the sampling technique used, by using iteration formula obtained by respondent with amount 116 costumer library. Data method using, questionnaire, interview, and documentation. Methods of data analysis are multiple linear regression  and descriptive percentage. Results showed the multiple linear regression equation is: Y ꞊ -3,489 + 0,242PK + 0,514TR + 0,519KP + 0,475FP + e. The results showed that collection processing , library layout, library management competence, and library facilities had a direct positive effect on the quality of Wonosobo library with total effect is 79,2%. Library layout give the biggest influence with 22,27%, collection processing with 13,76% total effect, management competence give influence 13,39%, and library facilities give less effect with 11,15% total effect